The Sidon’s/Ṣaydā Northern Hinterland during the Early Byzantine–Early Islamic Transition - Gwiazda, Mariusz; Piątkowska-Małecka, Joanna; Wicenciak, Urszula; Makowski, Piotr; Barański, Tomasz (2021)
The paper focuses on the archaeological evidence for settlement, cultural, and economic change in the Sidon’s (Ṣaydā) northern hinterland in the period of transition from early Byzantine to early Islamic times (7th-8th century c.e.). The changes were reconstructed based on the outcome of archaeological research at the sites of Porphyreon (modern Jiyeh) and Chhîm in the Sidon’s/Ṣaydā economic hinterland. The evidence confirms a continuity, although in reduced form, of occupation after the Arab conquest and a complete abandonment in the second half of the 7th or the beginning of the 8th century. The situation here bears similarity to other parts of Phoenicia, struck at the time with a settlement crisis that resulted in both a reduction of the population and a decline in the importance of cities, among others. These events were not sudden; they resulted from a process lasting several decades and impacting mainly the coastal area.
Keywords: Phoenicia; Sidon; early Byzantine period; early Islamic period; Settlement; Transition; Village